Exploring the feasibility of dimethyl ether (DME) and LPG fuel blend for small diesel engine: A simulation perspective - Nguyen, Thoai Anh; Pham, Thi Yen; Le, Huu Cuong; Nguyen, Van Giao; Nguyen, Lan Huong (Center of Biomass & Renewable Energy (CBIORE), 2024)
There is a looming global crisis owing to the increase in greenhouse gases and the escalating fossil fuel process. The issue is further compounded by the ongoing conflicts in different places in the world. Hence, there is an urgent need for a bouquet of alternative fuels suitable to power the incumbent internal combustion engine. Among various options available Dimethyl Ether (DME) is a friendly environment fuel, easy to liquefy, and suitable for use in diesel engines, while Liquefied Petroleum Gas (LPG) is another potential alternative fuel suitable for internal combustion engines. The present study is an endeavor to investigate the characteristics of a diesel engine powered with DME-diesel blends as pilot fuel while LPG was used as the main fuel. During engine testing, different blends of diesel-DME were used containing 0%, 25%, 50%, and 75% DME. The AVL Boost software was employed for modeling the engine performance and tailpipe emission. The test fuel combination was successful in running the engine sans any abnormality in sound or performance. The results showed carbon monoxide (CO) and hydrocarbon (HC) emissions were reduced using the test fuel combination while there was a marginal increase in the oxides of nitrogen (NOx) levels. In general, the combination of DME and LPG could be considered as a potential and promising solution to reducing pollutant emissions.